Legal effects on shareholders who do not make capital deposits in limited liability companies (Case Study of Case Decision Number 191/Pdt.G.2020/PN.Bgr.) - Revi Laracaka (Trigin Publisher, 2023)
This research examines the provisions regarding capital payment, the legal status of shareholders who fail to fulfill their capital payment obligations in a limited liability company, and analyzes the judge's considerations in stating that Edy Susanto is not entitled to be recognized as a shareholder because he has never made actual capital payment into the company. The results of this research indicate that according to the Company Law, capital payment provisions must be fulfilled in full and cannot be paid in installments after the Limited Liability Company is legally established. Shareholders who have never made capital payment after the establishment of the Limited Liability Company cannot be recognized as legitimate shareholders, and the judge's consideration in stating that Edy Susanto cannot be recognized as a shareholder of PT Berdikari Sukses Makmur is an appropriate consideration. To prevent such issues from occurring in the future, the government should improve the provisions in the Company Law by stating that if there is a violation of capital payment, the directors responsible for the violation of capital payment provisions should be held accountable, and the company should have the authority to demand such obligations through negotiation or legal action.